2021
DOI: 10.18332/tpc/134751
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tobacco screening and counseling in a large, midwestern pediatric emergency department

Abstract: INTRODUCTION The study objective was to assess tobacco screening and cessation counseling practices of pediatric emergency department (PED) and urgent care (UC) nurses and physicians, and factors associated with these practices. Secondarily, we assessed factors associated with performing tobacco smoke exposure reduction and tobacco cessation counseling. METHODS We conducted a cross-sectional survey of 30 PED/UC nurses and physicians working at one large, urban, Midwestern children's hospital. Measures include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Overall, PED/UC professionals’ adherence to the Clinical Practice Guideline of Treating Tobacco Use and Dependence [ 17 ] were mixed, and those who performed tobacco counseling usually only performed the “ask” and “advise” steps. This aligns with prior research that indicates ED professionals often “ask” and “advise,” but infrequently proceed to the next three steps [ 22 , 37 39 ]. Further, PED/UC professionals noted that they are not skilled beyond asking and advising due to the barriers of lack of training and resources.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, PED/UC professionals’ adherence to the Clinical Practice Guideline of Treating Tobacco Use and Dependence [ 17 ] were mixed, and those who performed tobacco counseling usually only performed the “ask” and “advise” steps. This aligns with prior research that indicates ED professionals often “ask” and “advise,” but infrequently proceed to the next three steps [ 22 , 37 39 ]. Further, PED/UC professionals noted that they are not skilled beyond asking and advising due to the barriers of lack of training and resources.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, parents are satisfied with receipt of the “5 A’s” from PED/UC professionals during their children’s visits [ 15 ]. However, research indicates that PED/UC professionals do not regularly screen for or systematically follow evidence-based guidelines to address parental tobacco use and child TSE [ 3 , 22 27 ]. There is a need to understand why there is suboptimal delivery of evidence-based guidelines by PED professionals in order to develop strategies for implementing and sustaining consistent adherence to these guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of consistent tobacco screening provision in health care settings has been attributed to limited knowledge and training of treatment providers [ 36 , 37 , 38 , 39 , 40 , 41 ]. For example, a recent study reported that 90% of surveyed health care providers did not have recent tobacco counseling training within the last 12 months, and 73.3% of them were unaware of evidence-based brief interventions for tobacco dependence that included asking patients about their use [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of consistent tobacco screening provision in health care settings has been attributed to limited knowledge and training of treatment providers [ 36 , 37 , 38 , 39 , 40 , 41 ]. For example, a recent study reported that 90% of surveyed health care providers did not have recent tobacco counseling training within the last 12 months, and 73.3% of them were unaware of evidence-based brief interventions for tobacco dependence that included asking patients about their use [ 36 ]. Limited training and a lack of standardized screening procedures for tobacco use disorder have significant impacts on intervention provision, as can the perception of limited time to provide preventive screening services if not related to the patient’s chief complaint [ 31 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation